2021
DOI: 10.1038/s41588-021-00887-y
|View full text |Cite
|
Sign up to set email alerts
|

The HIF complex recruits the histone methyltransferase SET1B to activate specific hypoxia-inducible genes

Abstract: Hypoxia-inducible transcription factors (HIFs) are fundamental to the cellular adaptation to low oxygen levels but it is unclear how they interact with chromatin and activate their target genes. Here we use genome-wide mutagenesis to identify genes involved in HIF transcriptional activity, and define a requirement for the histone H3 lysine 4 (H3K4) methyltransferase SET1B. SET1B loss leads to a selective reduction in transcriptional activation of HIF target genes, resulting in impaired cell growth, angiogenesi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 62 publications
(75 reference statements)
0
37
1
Order By: Relevance
“…Pol II that has initiated transcription and paused is characterized by S5 phosphorylation of the CTD (S5P), whereas S2 phosphorylation (S2P) is associated with Pol II pause release 16 . Several studies have demonstrated hypoxia-induced RNA Pol II CTD phosphorylation or CDK9 recruitment to HREs 11 , 13 , 42 , 43 . To determine whether DNA-PKcs or TRIM28 regulates release of paused Pol II during HIF-mediated transactivation, we performed ChIP-qPCR assays after exposure of cells to 20% or 1% O 2 for 16 h. Hypoxia significantly increased occupancy of the ANGPTL4 and PDK1 gene HREs in NTC cells by total Pol II, Pol II-S2P and Pol II-S5P, but only Pol II-S2P occupancy was significantly decreased in TRIM28-KD or DNA-PKcs-KD subclones of SUM159 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Pol II that has initiated transcription and paused is characterized by S5 phosphorylation of the CTD (S5P), whereas S2 phosphorylation (S2P) is associated with Pol II pause release 16 . Several studies have demonstrated hypoxia-induced RNA Pol II CTD phosphorylation or CDK9 recruitment to HREs 11 , 13 , 42 , 43 . To determine whether DNA-PKcs or TRIM28 regulates release of paused Pol II during HIF-mediated transactivation, we performed ChIP-qPCR assays after exposure of cells to 20% or 1% O 2 for 16 h. Hypoxia significantly increased occupancy of the ANGPTL4 and PDK1 gene HREs in NTC cells by total Pol II, Pol II-S2P and Pol II-S5P, but only Pol II-S2P occupancy was significantly decreased in TRIM28-KD or DNA-PKcs-KD subclones of SUM159 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Chromatin immunoprecipitation (ChIP)-chip microarrays [48][49][50] and ChIP-seq [35,40,42,45,[51][52][53][54][55][56][57][58] have identified thousands of HIF binding sites across the genome, with HIF binding at hypoxia response element (HRE) at promoter proximal and distal regions. These analyses demonstrate cell type variations in HIF binding profiles.…”
Section: Genomic Approaches Used In Hypoxia Researchmentioning
confidence: 99%
“…ChIP-seq studies have shown hypoxia induces redistribution of the histone methylation landscape co-ordinating changes in hypoxia gene expression [40,[61][62][63][64]. This work has contributed to the identification of specific JmjC histone demethylases, namely lysine demethylase 6A (KDM6A) and KDM5A, as oxygen sensors [62,64], determining the dependence of SET1B on H3K4me3 and gene expression changes in hypoxia [40], and elucidating the role of KDM4B and KDM6B in regulating hypoxic VEGFA expression and angiogenesis [43]. Furthermore, genome wide mapping of H3K27ac, a histone modification associated with transcriptionally active/poised genes, finds hypoxia induces changes in H3K27ac at gene loci correlating with effects of hypoxia on gene expression [42].…”
Section: Genomic Approaches Used In Hypoxia Researchmentioning
confidence: 99%
“…COVID-19 related-hypoxia manifests insufficient levels of oxygen supply in various tissues. SET1B activation is oxygen-dependent and facilitates hypoxia responses via site-specific histone methylation (240). In response to hypoxia, SET1B is recruited to the hypoxia-inducible transcription factor (HIF) promoter via HIF1a and facilitates the expression of genes involved in angiogenesis (240), one of the clinical features of COVID-19 severity.…”
Section: Writing Histone Modification: Role Of Hats and Hmtsmentioning
confidence: 99%
“…SET1B activation is oxygen-dependent and facilitates hypoxia responses via site-specific histone methylation (240). In response to hypoxia, SET1B is recruited to the hypoxia-inducible transcription factor (HIF) promoter via HIF1a and facilitates the expression of genes involved in angiogenesis (240), one of the clinical features of COVID-19 severity. HIF-related genes will be described further in a later section of histone demethylation.…”
Section: Writing Histone Modification: Role Of Hats and Hmtsmentioning
confidence: 99%